Association of patient risk factors and frequency of nevus-associated cutaneous melanomas - Hänßle, Holger; Mograby, Nerjes; Ngassa, Anni; Buhl, Timo; Emmert, Steffen; Schön, Michael; Rosenberger, Albert; Bertsch, Hans Peter (JAMA dermatology, 2016)
Importance The reported frequencies of associations between primary cutaneous melanomas and melanocytic nevi vary widely between 4% and 72%. However, earlier histopathologic studies were limited by their retrospective design and did not assess the influence of important patient-related risk factors. Objectives To identify the frequency of nevus-associated melanomas and correlate patient- and melanoma-related factors. Design, Setting, and Participants A prospective, single-center, observational study with systematic documentation of melanoma risk factors, clinical and dermoscopic criteria of excised lesions, and results of histopathologic examination was conducted at a university-based dermatology clinic. Participants included 832patients at high risk for developing melanoma. Evaluation was performed at regular intervals between April 1, 1997, and May 31, 2012, and data analysis was conducted between September 1, 2012, and December 31, 2013. Main Outcomes and Measures Assessment of the frequency of nevus-associated melanoma and the influence of patient- and melanoma-related factors on their manifestation. Results During the study, 190 melanomas (81 [42.6%] in situ and 109 [57.4%] invasive) were diagnosed in 113 of the 832 patients (13.6%); there were 42 women (37.2%) and 71 men (62.8%). The median (SD) Breslow thickness of invasive melanomas was 0.42 (0.43) mm. Histopathologic examination revealed remnants of melanocytic nevi in 103 melanomas (54.2%). Most nevus-associated melanomas were found on the trunk (67 [65.1%]); however, statistical significance for the localization was not present (P = .06). In univariate analyses, reported as odds ratios (95% CIs), nevus-associated melanomas were found significantly more frequently in patients of lower melanoma risk (risk group 1 [>50 common and/or ≤3 atypical nevi], 2.75 [1.14-6.64];P = .02), with more than 100 nevi (1.63 [1.02-3.60];P = .04), or with the diagnosis of in situ melanoma (14.01 [6.14-31.96];P < .001). In contrast, nevus-associated melanomas were found significantly less frequently in patients with 1 or more previous melanomas (0.28 [0.21-0.83];P = .005). All other factors (eg, age, skin type, hair color, and melanoma thickness) showed no significant influence on the manifestation of nevus-associated melanomas. These observations were confirmed in a separate analysis including all 109 invasive melanomas. Multivariate regression analysis identified 3 independent patient-related factors (high nevus count, low risk for melanoma, and female sex) and 1 melanoma-related factor (in situ melanoma) to be indicative of a significantly increased probability of nevus-associated melanomas. Conclusions and Relevance In this prospective study of a high-risk patient cohort, 54.2% of primary melanomas were associated with melanocytic nevi. Patients with many nevi and without previous melanomas or traits of familial atypical mole and multiple melanoma syndrome had a higher frequency of nevus-associated melanomas. These patients could thus benefit from sequential digital dermoscopy in addition to total-body photography.
Published online: November 4, 2015
Gesehen am 07.09.2020